Development of powtoon animation learning media in improving understanding of mathematical concept - Rizkiana Akmalia; Fajriana Fajriana; Rohantizani Rohantizani; Hayatun Nufus; Wulandari Wulandari (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The purpose of this development research is to determine the feasibility and effectiveness of using Powtoon animation learning media for flat-sided geometry. The development model used is the ADDIE model. The subjects of this study were students of class VIII-2 MTsS Syamsuddhuha (junior high religious school). The percentage results of product assessment by media experts are 96% in the very feasible category, the percentage result of product assessment by material experts is 92% in the very feasible category, and the percentage result of product assessment by 10 small group students is 94% in the very feasible category. Based on the results of the product assessment by all validators who stated that it was very feasible, the Powtoon animation learning media developed had meet the criteria for use for students. The effectiveness of using the product can be seen from the results of the comparison of the students' average pretest and posttest scores. The resulting product is effective in increasing the understanding of mathematical concepts, as evidenced by the average pretest score of 43,44, an increase in the posttest of 84,27, and the N-Gain value of 0,72 in the high category. It can be concluded that Powtoon animation learning media is feasible and effective to be used in improving the understanding of mathematical concepts.